Ficus citrifolia, Shortleaf Fig - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana; Robert J. Northrop (EDIS)
FOR 266, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, Heather V. Quintana, and Robert J. Northrop, describes this semi-deciduous fig tree that is native to Florida and naturally found in tropical hammocks throughout south Florida, the Caribbean, the Bahamas, the West Indies and some regions in Central America – scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.